Relation of Hysterectomy with Urinary Incontinence: Relation of Hysterectomy with Urinary Incontinence - Seemab, Saba; Nisar, Mehwish; Khan, Muhammad Waqas; Azam, Humaira; Qadir, Zaheer; Tariq, Maria; Mustafa, Muhammad; Karim, Suhail (Pakistan BioMedical Journal, 2022)
Urinary incontinence is defined by international continence society as “a condition in which involuntary loss of urine is objectively demonstrable and is a social hygiene problem “It refers to the involuntary leakage of urine can be associated with a systemic complication. Its prevalence is higher in women than in men thought it can affect men and women equally. It has the high prevalence due to its impact on the quality of life. The presence of urinary incontinence can be associated with anger; embarrassment related to any clinical condition, with loss of self-esteem and decrease motivation and decrease social, physical quality of life. Moment plausibility is that the bladder is presently overactive because of the surgery or changes in the pelvic floor musculature related with hysterectomy. Urge incontinence causes spillage of urine all of a sudden, related with critical ness and the powerlessness to smother such inclinations. Objective: Aim of this study is to determine urinary incontinence in women with hysterectomy. To assess the impact of urinary incontinence on quality of life of women undergone hysterectomy. Background: Furthermore, this study highlighted the presence of pain, discomfort, alteration of Quality of life and functional limitation due to incontinence of urine associated after Hysterectomy. An observational survey from different hospitals of Rawalpindi and Islamabad was conducted to collect relevant information. Methods: Standard questionnaire tools (UDI-6) and (KHQ) was used to collect data from 100 women using convenient random sampling technique in different hospitals of Rawalpindi and Islamabad. Results: The result revealed that urinary incontinence in women with hysterectomies strongly associated with altered quality of life causing loss of self-esteem leading to an impairment. Conclusion: This study concluded urinary incontinence associated with hysterectomy had pronounced effects on quality of life of women causing physical, social and psychological role limitations and participation restriction.